New-value Logging in the Echo Replicated File System - Hisgen, Andy; Birrell, Andrew; Jerian, Charles; Mann, Timothy; Swart, Garret (1993)
The Echo replicated file system uses new-value logging. Echo’s use of new-value logging provides a clean separation of the internals of the system into one module that is concerned with logging and recovery, and another module that is concerned with accessing and updating the file system’s on-disk structures. The logging module provides a restricted form of transaction. The restrictions simplify its implementation but impose constraints on the file system module. The file system module easily satisfies these constraints, resulting in a good match overall.